ANALISA PENGARUH LEVERAGE DAN RETURN ON ASSET TERHADAP EARNING PER SHARE (STUDI KASUS PERUSAHAAN REAL ESTATE DAN PROPERTI DI INDONESIA) - Useng Lienardo; Andi Aswan; Muhammad Ali (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This study aims to analyze the effect of leverage (financial leverage, operating leverage) and return on assets of real estate and property companies on earnings per share. This study is based on the phenomenon that 40 real estate and property companies listed in the Indonesia Stock Exchange (IDX) had fluctuation on net profit from 2015 to 2019. The study uses times series data from 40 real estate and property companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The data collected were analyzed using multiple linear regression. The results of this study indicate that financial leverage did not affect earnings per share. The same is also found in operating leverage. For the return on assets variable, this study found that it can be used to predit earnings per share.